Forensic Assistance Project: Consultant Report 1999-053 Konjic II Federation Commission on Missing Persons - Croat Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Stuart, Gary On 10 and 11 September 1999 the Federation Commission on Missing Persons - Croat Side exhumed the remains of 13 individuals from eight separate locations in and around the city of Konjic. The purpose of the exhumations was to identify or verify identities of a reported 13 missing elderly Bosnian Croat civilians in the Konjic area who were allegedly killed by Bosniak soldiers during hostilities in 1993. Five of the human remains were exhumed from single marked graves in cemeteries in Konjic and Sarajevo. Three of the individuals were exhumed from an unmarked joint grave in a cemetery in the village of Orahovica. Five of the remains were exhumed from single unmarked non-cemetery graves at widely separated sites in the Konjic region. Most of the individuals recovered in this exhumation are reported to be elderly civilian men and women who were killed in 1993 during hostilities in the Konjic between Bosniak soldiers and Bosnian Croat paramilitary soldiers. Place of Exhumation: Konjic Exhumation Site: Čelebići, Orahovica, Donje Selo, Gorani, Gornji Nevizdraci, Buturović Polje, Miljevići Cemetery Date of Exhumation: 10 September 1999 Minimum Number of Exhumed Individuals: 013